2017
DOI: 10.1016/j.jsha.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of coronary artery calcification on percutaneous coronary intervention and postprocedural complications

Abstract: CCS measured by MDCT has an important role in predicting early, but not late, complications from PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Previous reports have focused on outcomes after PCI for calcified lesions only in patients with stable angina 19,20 . Calcified plaques often require high‐pressure dilatation to gain an acceptable lumen area.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have focused on outcomes after PCI for calcified lesions only in patients with stable angina 19,20 . Calcified plaques often require high‐pressure dilatation to gain an acceptable lumen area.…”
Section: Discussionmentioning
confidence: 99%
“…Calcification is a special manifestation of CVD that induces major arterial stiffening and occlusions. Severe coronary artery calcification increases the risks of interventional procedures, and patients have a poor prognosis [2]. Diabetes mellitus is a primary cause of vascular calcification [3].…”
Section: Introductionmentioning
confidence: 99%
“…Previous report demonstrated that sustained severe dissection occurred in 1.4% among 3622 PCIs to complex lesions (thrombus, calcification, bifurcation or CTO) [ 34 ]. As for calcification lesions, coronary dissections which required further stent deployment or prolonged balloon inflation occurred in 4.8% of PCI to severe calcificated lesions [ 35 ]. Although the definition of complex PCI and coronary dissection were different from the definitions in these reports, the incidence of severe CICAD in patients with complex PCI was 1.6% in our registry, which was similar to the previously reported incidence.…”
Section: Discussionmentioning
confidence: 99%